Use of Social Media Tools by Undergraduates: Students and Teachers’ Perspective (Journal of Social Sciences Review, 2023)
This study explores the use of social media tools by undergraduate students and teachers from their perspectives. A mixed-methods research approach, which includes a survey of 150 students and interviews with ten teachers at the University of Gujrat, was used. The study found that social media tools are widely applied by undergraduate students, with Facebook being the most popular platform. Students use social media primarily for communication with peers, sharing of academic resources, and entertainment. Teachers also use social media, but less frequently than students, and for professional development and communication with colleagues. The results indicate that social media has a significant negative impact on the quality of education, with students reporting increased distraction and reduced academic performance due to excessive use of social media. The research also discovered that the students who spent more time on social media were more likely to experience anxiety and depression, which further affected their academic performance. The findings suggest that universities need to take a more proactive approach to address the negative effects of social media on education, including providing guidance and support to students on how to use social media in a more responsible and productive manner.
Keywords: Educational Sustainability; Quality Education; Social Media Tools; Deterioration